2013
DOI: 10.1007/s00253-012-4674-z
|View full text |Cite
|
Sign up to set email alerts
|

Indole and 7-benzyloxyindole attenuate the virulence of Staphylococcus aureus

Abstract: Human pathogens can readily develop drug resistance due to the long-term use of antibiotics that mostly inhibit bacterial growth. Unlike antibiotics, antivirulence compounds diminish bacterial virulence without affecting cell viability and thus, may not lead to drug resistance. Staphylococcus aureus is a major agent of nosocomial infections and produces diverse virulence factors, such as the yellow carotenoid staphyloxanthin, which promotes resistance to reactive oxygen species (ROS) and the host immune system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 44 publications
1
91
0
Order By: Relevance
“…Consequently, we searched for new indole derivatives that inhibit biofilm formation rather than only cell growth to reduce the risk of drug‐resistance development. Previously, we have shown that 7‐benzyloxyindole had antivirulence activity and antibiofilm activity against persistent S. aureus infections in vitro (Lee et al ., 2013). In the present study, we studied benzyloxy and fluoro‐substituted indoles, and found that benzyloxy group is essential for antibiofilm activity against the fluconazole‐resistant Candida strain (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we searched for new indole derivatives that inhibit biofilm formation rather than only cell growth to reduce the risk of drug‐resistance development. Previously, we have shown that 7‐benzyloxyindole had antivirulence activity and antibiofilm activity against persistent S. aureus infections in vitro (Lee et al ., 2013). In the present study, we studied benzyloxy and fluoro‐substituted indoles, and found that benzyloxy group is essential for antibiofilm activity against the fluconazole‐resistant Candida strain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In Pseudomonas putida , signalling molecules such as indole enhances TtgGHI efflux pump that are relevant for antibiotic resistance (Molina‐Santiago et al ., 2014). The previous studies have reported that indole inhibits biofilm formation and suppresses the virulence of bacterial strains such as Staphylococcus aureus , Agrobacterium tumefaciens (Lee and Lee, 2010; Lee et al ., 2013, 2015a,b; Lee et al ., 2016) and Vibrio cholera (Mueller et al ., 2009). Likewise, indole derivatives such as 7‐fluoroindole, 7‐hydroxyindole, 3‐indolyl acetonitrile and 2‐aminobenzimidazoles have been reported to exhibit antimicrobial activities against pathogenic bacteria (Lee et al ., 2009, 2011, 2012, 2015a,b; Frei et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that a plant flavone (Lee et al 2012) and a bacterial signaling molecule indole (Lee et al 2013) reduced the production of staphyloxanthin and α-hemolysin.…”
Section: Introductionmentioning
confidence: 99%
“…Highly expressed genes coding for proteases, molecular chaperones and TCA cycle enzymes in the presence of indole might play crucial roles in indole-induced stress conditions. Indole has been reported to act as an antivirulence compound against E. coli, Pseudomonas aeruginosa and Staphylococcus aureus (Lee et al, 2007(Lee et al, , 2009(Lee et al, , 2013Chu et al, 2012). Indole reduced virulence factors by modulating the expression of virulence and regulatory genes, which were reportedly regulated by the QS system in P. aeruginosa (Lee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%